THE PROBLEMS OF THE SYSTEM OF COST ACCOUNTING IN BANKS OF THE SECOND LEVEL - Zh. T. Yeveskina,; M. Zh. Zharylkassinova, (Academic Journal of Physical and Chemical Sciences, 2019)
As you know, the role of the banking sector is great. In modern conditions of financial market development, banks are the main source of financing for various sectors of the economy, such as industry, trade, agriculture, etc., and also have a great importance in protecting the country from financial crises. On this basis, the need to apply a cost accounting system in such a vital sector is important, in order to control costs, measure the costs of various processes and provide the necessary analytical and detailed data based on scientific standards to make informed decisions. The article discusses the role and importance of the formation of an effective cost accounting system in banks, as well as the problems of calculating the costs of banking operations in Kazakhstan.